Linguistic Distance and Bridge Language Effects on Equity Ownership in Cross-Border Acquisitions - Ilya CUYPERS, (Institutional Knowledge at Singapore Management University, 2014)
We study the effects of language distance and bridge language proficiency on the level of equity taken by acquirers from 67 countries in 59,092 acquisition targets in 69 host countries. We theorize and find that both language distance and bridge language proficiency affect the level of equity an acquirer takes in a target. In addition to its direct effect, language distance also moderates the effect of bridge language on the level of equity taken. Our results clearly demonstrate that governance research and international business studies can benefit from incorporating language into their explanatory models.